PEMEROLEHAN BAHASA IBU DAN INTELIGENSI ANAK DENGAN HASIL BELAJAR BAHASA INDONESIA - Kornelius Rulli Jonathans (The Way Jurnal Teologi dan Kependidikan, 2021)
Abstract The purpose of this study was to determine the effect of Acquisition of Mother Language and Child Intelligence together on Indonesian Language Learning Outcomes. The results showed the effect of mother tongue acquisition and children's intelligence together on Indonesian learning outcomes with the regression equation Ŷ = 9.120 + 1.654X1 + 0.338X2, with a correlation coefficient = 0.884 with a significance level of  = 5% and the determinant coefficient = 78,10%. From the regression equation, it can be interpreted that the Indonesian Language Learning Outcomes score. The constant value = 9,120 indicates that the lowest mother tongue language acquisition (X1) and children's intelligence (X2) conditions do not allow the child to obtain high Indonesian Language Learning Outcomes (Y). The test results obtained regression coefficients of 1.654 and 0.338 indicating a positive effect. From the analysis of the scores on the Indonesian learning test results show that learninglanguage in Kindergarten is less directed towards developing language skills as a whole, but rather emphasizes receptive abilities; listening and reading are relatively good, while the ability is productive; speaking and writing is very lacking, because the child can speak fluently when doing free speech, but when talking is based on lesson themes, the child's speaking ability is a bit choked up, so is writing, because it is only intended to train the child's fine motor skills not intended to develop language skills.